Pengaruh Faktor Psikologis Konsumen Terhadap Keputusan Pembelian Pada Produk Iphone - Nesti Wulandari; Ahmad Dardiri; Paula Candra; Nur Novita Sari (LPPM STIA Lancang Kuning Dumai, 2023)
This research examines the influence of psychological factors on consumer purchasing decisions regarding iPhone products. The factors studied include motivation, perception, learning, and consumer attitudes. The method used is a quantitative approach with a positivist perspective. The research sample consists of 100 randomly selected iPhone users. Data is collected using a research instrument consisting of questions measured using a Likert scale. Data analysis is conducted using multiple linear regression analysis. The research findings indicate that motivation, perception, learning, and attitude have a significant positive influence on consumer purchasing decisions regarding iPhone products. Consumer motivation, such as physiological needs, security, social needs, and ego needs, are factors that drive consumers to purchase iPhone products. Consumer perception of quality, product variety, and the iPhone brand image also influences purchasing decisions. Consumer learning about information and iPhone products, as well as a positive attitude towards the iPhone brand, also affect purchasing decisions. This research provides a deeper understanding of consumer behavior in the context of smartphone purchases, specifically regarding iPhone products. The findings of this research can serve as a reference for iPhone brand managers in designing effective marketing strategies to attract consumer interest and improve purchasing decisions.